The association of mitochondrial DNA haplogroups with POAG in African Americans. (April 2019) - Gudiseva, Harini V.; Pistilli, Maxwell; Salowe, Rebecca; Singh, Larry N.; Collins, David W.; Cole, Brian; He, Jie; Merriam, Sayaka; Khachataryan, Naira; Henderer, Jeffrey; Addis, Victoria; Cui, Qi N.; et al.
Abstract: Mitochondrial dysfunction has been implicated in the pathogenesis of primary open-angle glaucoma (POAG). However, the potential significance of mitochondrial DNA (mtDNA) haplogroups to POAG has not been evaluated in the overaffected African American population. To investigate the association of mtDNA haplogroups with POAG and its phenotypic characteristics, genotyping data from 4081 African American subjects (1919 cases and 2162 controls) was analyzed using 1293 positions on mtDNA. The overall frequency of mtDNA haplogroups in the Primary Open-Angle African American Glaucoma Genetics (POAAGG) study cohort was 37% L3, 29% L2, 21% L1, 4% L0, and 10% non-African haplogroups (non-L). When all haplogroups (L0, L1, L2, and non-L) were compared against theL3 reference group, after adjusting by age and principal component of ancestry, the non-L3 haplogroups showed higher risk of POAG (OR-1.19, p = 0.02), with a particularly strong association among males (OR = 1.41, p = 0.003). More specifically the non-L group was associated with higher POAG risk than the L3 haplogroup (OR = 1.77, p = 0.007, Bonferroni adjusted p = 0.027) and to the L3e (n = 256, OR = 1.92, p = 0.007, Bonferroni adjusted p = 0.029). No significant association was found when genders were analyzed together or in female only analysis. There were no significant differences in various POAG endophenotypes across mtDNA haplogroups. This study expands our knowledge of mitochondrial genetics and mtDNA haplogroup associations in African American POAG. Further work is needed to better understand the functional role of mtDNA polymorphisms and their interactions with nuclear genes that affect POAG.